Pendampingan dan Sosialisasi Pembentukan Koperasi Nagari Merah Putih Nagari Kudu Gantiang Kabupaten Padang Pariaman - Gusminarti, Gusminarti; Fithrina, Hendria; Khairani, Khairani; Yuslim, Yuslim; Rosari, Anton; Romi, Romi; Darnis, Darnis; Fatimah, Titin; Zulfitri, Amelia; Syofiarti, Syofiarti; Andora, Hengki; Delyarahmi, Sucy; Warman, Kurnia; Fendri, Azmi (LPPM Universitas Dharma Andalas, 2025)
Based on Presidential Instruction No.9/2025 the President ordered each village to form a Merah Putih Village Cooperative. Therefore, the Government of Nagari Kudu Gantiang in collaboration with the Department of State Administration Law, Faculty of Law, Andalas University conducted community service related to the establishment of the Merah Putih Nagari Cooperative. This activity aims to assist and socialize the formation of the Nagari Merah Putih Cooperative in Nagari Kudu Gantiang as an effort to strengthen the community-based economy. The method used is in the form of socialization and assistance in the formation of the Nagari Merah Putih Cooperative in Nagari Kudu Gantiang. The result of this service is that the Nagari Merah Putih Cooperative of Nagari Kudu Gantiang has been established as a revitalization of the Kudu Gantiang Village Unit Cooperative (KUD) which has not carried out its business activities for a long time.